Comparative analysis acts of international legal regulation of patient’s rights - Козаченко, Ю. А. (Theory and practice of jurisprudence, 2016)
In the article, there have been presented the results of the research of the international legal acts regulating citizens’ rights in the sphere of health protection, namely patients’ rights. The article contains analysis of General Declaration of Human Rights (1948), Declaration on Policy in the Field of Patient Rights Securing in Europe (1994), European Charter of Patients’ Rights (2002) and others acts of international legal regulation of patient’s rights.